Reforming the Prohibition of Concurrent Office-Holding by Deputy Ministers in Indonesia's State Ministry Law: Mereformasi Larangan Merangkakkan Jabatan oleh Wakil Menteri dalam Undang-Undang Kementerian Negara di Indonesia - Rizqi Fadhlillah, Muhammad; Yusuf, Yusmedi; Aji Pangestu, Ilham (Mendapo: Journal of Administrative Law, 2026)
This study examines the legal lacuna concerning the prohibition of concurrent office-holding by Deputy Ministers under the State Ministry Law and the urgency of reconstructing its regulatory framework to ensure legal certainty. The issue has become increasingly significant following Constitutional Court Decision Number 128/PUU-XXIII/2025, which affirmed that the prohibition on concurrent office-holding applicable to Ministers also extends to Deputy Ministers. Nevertheless, this prohibition has not yet been explicitly incorporated into statutory regulations, thereby creating legal uncertainty in governmental practice. This research employs a normative legal method using statutory, case, and conceptual approaches. The primary legal materials consist of the Constitution of the Republic of Indonesia of 1945, the State Ministry Law, Constitutional Court decisions, and relevant legal literature. The findings reveal that the absence of an explicit legal norm governing the prohibition of concurrent office-holding by Deputy Ministers may give rise to conflicts of interest, weaken accountability principles, and reduce the effectiveness of public administration. The novelty of this study lies in its proposal for a legal reconstruction of the State Ministry Law through the insertion of an explicit provision prohibiting concurrent office-holding by Deputy Ministers as a legislative follow-up to the Constitutional Court's decision. Such reconstruction is necessary to strengthen legal certainty, prevent abuses of power, and provide a firmer legal basis for the imposition of sanctions against Deputy Ministers who violate the prohibition.